FRUIT-BERRY FILLERS IN THE PRODUCTION OF KAZAKH NATIONAL FERMENTED MILK DRINKS - А. А. Shunekeyeva; M. K. Alimardanova; A. A. Majorov (Academic Scientific Journal of Chemistry, 2021)
This paper offers investigation of fruit and berry fillers on the rheological properties of fermented milk drinks. The research was conducted as part of a scientific research effort. Local wild plants were used as fillers. This type of research allowed expanding the range of products at the enterprise and improving the organoleptic and nutritional properties of products. The purpose of this article is to find additional local vegetable raw materials as filler for fermented milk products. The importance of the results is that the data obtained can be used by specialists of dairy farms. During the period of coronavirus infection, when there were interruptions in the supply of raw materials, such directions it sets for future research as the development and improvement new food products by using local plant raw materials were revealed. The experimental samples of fermented milk drink from goat’s milk with various fillers (tayberry, shadberry, black chokeberry and blackcurrant). The pH of the samples were measured with a pH meter (Exspert-рН, Russia). Total solids, protein, fat, ash, and titratable acidity were determined according to the methods described by the standard method. Goat’s milk is subjected to ozonization for 10 minutes at an ozone concentration of 80 mg/m3 before entering the container. The pasteurized goat milk (at 37 °C) was inoculated with freeze-dried culture bacterial starter culture (thermophilic lactic acid bacteria and bifidobacteria (Breve B 10, Bifidobacterium adolescentis B 14, Bifidobacterium adolescentis B 37) in the ratio 2:1 at 5 % inoculation level. The sensory aspects were undertaken using 10 panellists. The degree of influence of the introduced bacterial starter culture on the duration of fermentation of fermented milk beverages was studied by taking into account the rheological characteristics and structural and technological parameters. A mathematical model of the dependence of the strength and acidity of a fermented milk clot on the dose of fruit and berry fillers is constructed